Population density and organic fertilization in fava bean from central Mexiquense - Flores Carrera, Laura Stephanie; Pérez López, Delfina de Jesús; Sangerman-Jarquín, Dora Ma.; Rubí Arriaga, Martín; González Huerta, Andrés; Ramírez Dávila, José Francisco (Revista Mexicana de Ciencias Agrícolas, 2022)
Two experiments were established in 2017 and 2018 in San Nicolás Guadalupe, San Felipe del Progreso, State of Mexico, to evaluate the effects of spacing between plants at 20, 30, 40 and 50 cm with the application of chicken manure, vermicompost, mushroom compost and 30N-60P-60K in cultivars identified as Xalatlaco, Calimaya and San Felipe. The 48 treatments were evaluated in a series of randomized complete block design experiments with three replications per year in a split plot arrangement. In the combined analysis, it was observed that in both years (A) there were highly significant differences (p= 0.01) in 13 variables. In 2017, the best phenotypic expression in plant height (PH), flowering (DF), pods per plant (NPP), weight of pods per plant (WPP), seeds per pod (NSP), clean seeds (NCS) and weight of clean seeds (WCS) were favored, compared to 2018, but the yield (YLD) in both years was 1.5 t ha-1. In densities (D), there were significant differences (p= 0.01) in 13 variables, and it was detected that at a distance between plants of 20 cm there was more NPP (18.5 cm), PH (1.4 cm) and HFP (47.5 cm); at 40 and 50 cm between plants, there was more NB and NPB. In the NCS, WCS and YLD characteristics, the same behavior appeared at 20, 40 and 50 cm. In organic fertilizers (F), there was a significant phenotypic differentiation (p= 0.01) in PH, NPP, WPP, WCS and YLD; with chicken manure higher PH and HFP were obtained. The mushroom compost favored WPP, NSS and weight of 100 seeds (W100S) and the vermicompost did it in NPP, WPP and WCS. The three cultivars (C) were significantly different (p= 0.01): Xalatlaco was better in efficiency (EFF), WPP, WCS, W100S and YLD (1.74 t ha-1).